VASYL STEFANYK – LESIA UKRAINKA: AN UNFINISHED DIALOGUE - Baran, Yevhen (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The study is devoted to the research of specifity of the literary communicationbetween Vasyl Stefanyk and Lesia Ukrainka in the form of an unfinished dialogue. The aim of the article is todisclose the peculiarities of relations between Vasyl Stefanyk and Lesia Ukrainka, foremost, the analysis is conducted in the bibliographical aspects of the research, namely the materials of O. Radavska “Lesia Ukrainka and Vasyl Stefanyk: literary relations, creative echoes”, of M. Moklytsia “Lesia Ukrainka’s aesthetics: the problem of an authorial notional dictionary”, of L. Vasylyk “Lesia Ukrainka and Vasyl Stefanyk: the semantics of the stony in the fictional world”, as well as major literary tendencies of their articles that lay in searches of creative echoes of the indicated authors, of the interpretation of creative work, of the research of stylistics and the system of image creation. However, the theme of relations between Vasyl Stefanyk and Lesia Ukrainka is still not exhausted and not explored to a full extent. The author performs the research on the basis of Lesia Ukrainka’s article “Writers-Rusyny in Bukovyna” (1899), giving it a detailed interpretation, of Lesia Ukrainka’s letters to Olha Kobylianskaand Mykhailo Kryvyniuk, and, respectively, of Vasyl Stefanyk’s letters to Wacław Moraczewski, Olha Kobylianska and others. That provides the practical significance and novely of the work. Consequently, the course of relations between Vasyl Stefanyk and Lesia Ukrainka is analysed in the chronological order, the writers’ attitude to the creative work of each other is elucidated, as well as mentions, recollections and fragments of the letters are commented.